A Mathematical, Graphical and Visual Approach to Granular Synthesis Composition - Souza, Fernando Falci de; Maia Jr., Adolfo (Revista Vórtex, 2021)
We show a method for Granular Synthesis Composition based on a mathematical modeling for the musical gesture. Each gesture is drawn as a curve generated from a particular mathematical model (or function) and coded as a MATLAB script. The gestures can be deterministic through defining mathematical time functions, hand free drawn, or even randomly generated. This parametric information of gestures is interpreted through OSC messages by a granular synthesizer (Granular Streamer). The musical composition is then realized with the models (scripts) written in MATLAB and exported to a graphical score (Granular Score). The method is amenable to allow statistical analysis of the granular sound streams and the final music composition. We also offer a way to create granular streams based on correlated pair of grains parameters.